You wouldn't want to be an Egyptian mummy! : disgusting things you'd rather not know - Stewart, David (David Evelyn), 1954-; Antram, David, 1958-; Salariya, David (New York : F. Watts, 2000)
A light-hearted approach to the process of mummification in ancient Egypt.
Includes index.
School Library Journal.
5.9
8.6.
3-6
Keywords: Mummies -- Egypt -- Juvenile literature; Mummies; Mummies; Egypt -- Antiquities; Egypt -- Antiquities